2014
DOI: 10.1155/2014/612147
|View full text |Cite
|
Sign up to set email alerts
|

The Enigma of the Tinnitus-Free Dream State in a Bayesian World

Abstract: There are pathophysiological, clinical, and treatment analogies between phantom limb pain and phantom sound (i.e., tinnitus). Phantom limb pain commonly is absent in dreams, and the question arises whether this is also the case for tinnitus. A questionnaire was given to 78 consecutive tinnitus patients seen at a specialized tinnitus clinic. Seventy-six patients remembered their dreams and of these 74 claim not to perceive tinnitus during their dreams (97%). This can be most easily explained by a predictive Bay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 37 publications
1
20
0
Order By: Relevance
“…The findings of this study can be interpreted in the context of the Bayesian brain to derive a model for tinnitus (De Ridder, Joos, & Vanneste, 2014;De Ridder, Vanneste, & Freeman, 2014;Hullfish, Sedley, & Vanneste, 2019;Lee et al, 2017;. Some individuals with HL develop tinnitus, which is characterized by increased information transmission efficiency in a network that comprises the lateral OFC, VLPFC, sgACC, and parahippocampal and hippocampal areas, as well as the insula.…”
Section: Discussionmentioning
confidence: 84%
“…The findings of this study can be interpreted in the context of the Bayesian brain to derive a model for tinnitus (De Ridder, Joos, & Vanneste, 2014;De Ridder, Vanneste, & Freeman, 2014;Hullfish, Sedley, & Vanneste, 2019;Lee et al, 2017;. Some individuals with HL develop tinnitus, which is characterized by increased information transmission efficiency in a network that comprises the lateral OFC, VLPFC, sgACC, and parahippocampal and hippocampal areas, as well as the insula.…”
Section: Discussionmentioning
confidence: 84%
“…hearing loss (De Ridder et al, 2014a;Lee et al, 2017). In the same context, we have recently reported that approximately 70% of patients with unilateral SSNHL experience ipsilesional tinnitus (Lee et al, 2017), indicating that missing auditory information (i.e., prediction error) may stimulate neural circuit interactions between lower-order (peripheral auditory input) and higher-order (prediction-driving process of auditory perception) auditory systems to reduce uncertainty in a bottom-up fashion due to sudden hearing deterioration.…”
Section: The Bayesian Inferential Network Updates Missing Auditory Inmentioning
confidence: 96%
“…Tinnitus, they propose, is due to deafferentation causing erroneous prediction. However, they suggest that during dreaming, this prediction error is not generated, abolishing the tinnitus [7] .…”
Section: Background To the Deafferentation Hypothesis And Proofs Of Cmentioning
confidence: 98%
“…Tinnitus can also be viewed as a ‘phantom sensation’ [7] . Interestingly, both insufficient and excessive sound exposure can result in tinnitus [1] .…”
Section: Background To the Deafferentation Hypothesis And Proofs Of Cmentioning
confidence: 99%